Addiction and change : how addictions develop and addicted people recover - DiClemente, Carlo C. (New York : Guilford Press, 2003)
"The stages-of-change model has become widely known as a framework for conceptualizing recovery. Less well known are the processes that drive movement through the stages or how the stages apply to becoming addicted. From Carlo DiClemente, codeveloper of the Transtheoretical Model, this book offers a panoramic view of the entire continuum of addictive behavior change. Illuminated is the common path that individuals travel as they establish and reinforce new patterns of behavior, whether they are developing an addiction or struggling to free themselves from one, and regardless of the specific addictive behavior. Presenting cutting-edge research with significant clinical implications, the book addresses crucial questions of why, when, and how to intervene to bolster recovery in those already addicted and reach out effectively to people at risk. It is essential reading for clinicians, prevention specialists, and policymakers."--BOOK JACKET.
Pt. I. Understanding Addictions in Terms of Change -- 1. Models of Addiction and Change -- 2. The Process of Human Intentional Behavior Change -- 3. The Well-Maintained Addiction: An Ending and a Beginning -- Pt. II. The Road to Addiction: The Journey Through the Stages of Addiction -- 4. Exploring the Precontemplation, Contemplation, and Preparation Stages of Becoming Addicted -- 5. Repeated and Regular Use: Moving from Preparation to Action on the Road to Addiction -- Pt. III. Quitting an Addiction: The Journey Through the Stages of Recovery -- 6. Precontemplation for Recovery: Cultivating Seeds for Change -- 7. The Decision to Change: Moving from the Contemplation to the Preparation Stage of Recovery -- 8. Preparing for Action: Creating a Plan -- 9. Taking Action to Change an Addiction -- 10. The Long Haul: Well-Maintained Recovery -- Pt. IV. Designing Interventions to Match the Process of Change -- 11. Prevention: Interfering with the Process of Becoming Addicted -- 12. Designing Interventions for Recovery -- 13. Research on Addiction and Change.
Includes bibliographical references (p. 281-310) and index.
Keywords: Substance-Related Disorders; Behavior, Addictive -- psychology